2023
DOI: 10.1007/s10875-023-01488-6
|View full text |Cite
|
Sign up to set email alerts
|

Inborn Error of STAT2-Dependent IFN-I Immunity in a Patient Presented with Hemophagocytic Lymphohistiocytosis and Multisystem Inflammatory Syndrome in Children

Abstract: Human inborn errors of immunity (IEI) affecting the type I interferon (IFN-I) induction pathway have been associated with predisposition to severe viral infections. Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening systemic hyperinflammatory syndrome that has been increasingly associated with inborn errors of IFN-I-mediated innate immunity. Here is reported a novel case of complete deficiency of STAT2 in a 3-year-old child that presented with typical features of HLH after mumps, measles, and rubel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Patients with virus-induced HLH may have abnormalities in the genes associated with the innate immune response to viral infections, especially in the IFN-1 pathway, such as STAT2, STAT1, IFNAR1, and IFNAR1. 22 STAT2 deficiency was elegantly reported by López-Nevado et al, 22 who suggested that these genes should be evaluated in patients with virus-induced HLH. Unfortunately, these abnormalities were not evaluated in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…Patients with virus-induced HLH may have abnormalities in the genes associated with the innate immune response to viral infections, especially in the IFN-1 pathway, such as STAT2, STAT1, IFNAR1, and IFNAR1. 22 STAT2 deficiency was elegantly reported by López-Nevado et al, 22 who suggested that these genes should be evaluated in patients with virus-induced HLH. Unfortunately, these abnormalities were not evaluated in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…The clinical histories of the IRF9‐and STAT2‐deficient patients have been described previously [14, 16]. The blood samples used in the experiments presented in this work were obtained during follow‐up analyses of immune cell function and responses to vaccination, at around 10 and 1 year of age for the IRF9‐deficient patients and about 3 years of age for the STAT2‐deficient patient.…”
Section: Methodsmentioning
confidence: 99%
“…We, and others, have previously identified and characterized patients with mutations inactivating IRF9 and STAT2 gene expression and shown that peripheral blood mononuclear cells (PBMCs) and fibroblasts from these patients do not upregulate ISG expression after IFNαβ stimulation [13–16]. Here we have addressed the importance of type I interferon signalling for human NK cell development and function by studying the phenotype and function of circulating NK cells isolated from these patients.…”
Section: Introductionmentioning
confidence: 99%